Global Restructuring, State, Capital and Labour - Bieler, A. author. aut Link
XII, 249 p.
Keywords: This book provides a critical engagement between contending historical materialist approaches that have played a crucial role in shaping post-positivist International Relations theory. It analyzes globalization as a process of state formation and argues that its fate depends on the neo-liberal recomposition of labour relations. .